Annulation of 1H-pyrrole-2,3-diones by thioacetamide: an approach to 5-azaisatins - Kobelev, Aleksandr I.; Stepanova, Ekaterina E.; Dmitriev, Maksim V.; Maslivets, Andrey N. (Beilstein Journal of Organic Chemistry, 2019)
A novel approach to 1H-pyrrolo[3,2-c]pyridine-2,3-diones (5-azaisatins) has been developed via an unprecedented annulation of pyrrolo[2,1-c][1,4]benzoxazine-1,2,4-triones by thioacetamide. A new way of C–H functionalization of thioacetamide has been discovered. The reaction proceeds under green catalyst-free conditions.
Keywords: annulation; domino reactions; isatin; nitrogen heterocycles; thioamides